Pengaruh Konsumsi Sari Kurma Pada Akhir Kehamilan Terhadap Kemajuan Persalinan Kala I Dan Jumlah Perdarahan Saat Persalinan Pada Primipara Di Wilayah Kerja Puskesmas Klaten Selatan - Suroso Suroso; Paryono Paryono (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Mother Maternity needed drinks and foods that contain lots of sugar elements, this is because of the amount of contraction of the muscles of the uterus when it will remove the baby, even more so if it takes a long time. Purpose of this study was to determine the effect of the consumption of palm juice at the end of pregnancy to the first stage of labor progress and the amount of bleeding during childbirth. The design of this study using a quasi-experimental design with the design of a static comparison group, sampling technique using purposive sampling approach, analysis of data Bivariate statistical tests using independent sample t-test. Hypothesis test results with respect to the progress of the first stage of labor is obtained t count -3.234 while t table at dk n-2 (58) was 2,002 so that Ho refused because -3.234> 2.002 means "no influence between the consumption of palm juice regularly in late pregnancy with progress first stage of labor in primiparous in the BPM area of South Klaten Klaten district. On the amount of bleeding obtained t count -3.131 while t table at dk n-2 (58) was 2,002 so that Ho refused because -3.131> 2.002 means "no influence between the consumption of palm juice regularly in late pregnancy with the bleeding amount of labor. In conclusion, there is the influence of the consumption of palm juice regularly in late pregnancy with the bleeding amount of labor.